Essays on Accounting – Compliance, Education and (Non-)Financial Reporting - Pleger, Alana Sarina; Justus Liebig University Giessen (My University, 2025)
This dissertation addresses current issues in financial accounting and comprises four research papers structured into three sections: Compliance (Section A), Accounting Education (Section B), and Financial and Non-Financial Reporting (Section C).
The empirical study in Section A examines the effect of two control design elements on employees’ performance misreporting behavior. The experimental findings suggest that ethical considerations can be reintegrated into employees’ decision-making depending on the design of control elements, specifically the presence of detrimental effects on others and the level of control result transparency.
The research paper in Section B evaluates the animated video series “Bibi Bilanzierung” as an edutainment-based teaching tool. Using survey data and a field experiment, the study finds that the video-based teaching concept increases students’ motivation and exam performance in an introductory accounting course.
Section C comprises two normative research papers on financial and non-financial reporting. Research Paper C1 analyzes corporate pay transparency reports following the introduction of the German Transparency in Wage Structures Act and derives best-practice recommendations. Research paper C2 examines the substance-over-form principle in parent-subsidiary relationships within German group accounting. Overall, the dissertation provides empirical and conceptual insights into the effective design and implementation of accounting instruments across education, control systems, and corporate reporting.
Keywords: Compliance; Misreporting; Accounting Education; Non-Financial Reporting; Financial Reporting; ddc:650; ddc:330